Гіпотиреоз у хворих на цукровий діабет 2-го типу як чинник збільшення ризику серцево-судинних захворювань - Приступюк, О. М. (Clinical Endocrinology and Endocrine Surgery, 2013)
The leading risk factors for cardiovascular lesions in patients with diabetes mellitus type 2 in combination with hypothyroidism, hypertension and dyslipidemia. TSH level in the blood plasma in 80% of patients is above the reference value. The age of onset of of hypothyroidism in male patients with diabetes mellitus type 2 on 10 years less than in female.